Structure and properties of the fusion zone formed due to electron beam facing of a coating from nitrogen-alloyed chromium-manganese iron on low-carbon steel; Metal Science and Heat Treatment; Vol. 49, iss. 1-2 - Narkevich N. A. (2007, 2007)
Title screen